Peningkatan Ketrampilan Dasar Penyusunan Tari Anak Kelompok MGMP Kesenian Dikabupaten Karanganyar - Katarina Indah Sulastuti (Institut Seni Indonesia Surakarta, 2016)
This paper suggests about efforts to improve basic skills in preparation for the group of children dance Subjects Teachers Council (MGMP) Art in the district of Karanganyar through Dance Child Development and Training. These actions are in principle also aims to improve the knowledge and conceptual understanding of the preparation for teachers of dance arts; improve the skills of a child preparation techniques of dance for art teachers in the district of Karanganyar; improve technical skills and innate dancing children for the sake of learning; provide refreshment materials for learning the art of formal dance that always follow the changing times; and liaison between the Department of Dance ISI Surakarta with alumni, and stakeholders (schools in the district Karanganyar).Improved preparation of dance skills for teachers of children is very important given the lack of art materials for teaching dance in elementary and junior. Through training activities are expected of teachers able to be creative dance untukmencipta children, to meet the needs of the art learning materials in schools. Preparation and Training Activities This dance is applying explorative and innovative methods, as methods in the preparation of material pembelajran danceÂ as art in elementary - junior high. A lecture and demonstration, as a method of dance training for groups in Karanganyar MGMP Art. This method has the advantage that it combines a variety ofÂ methods in a continuous flow of activities. Methods of providing support for other methods of optimizing these training activities.The method applied in the training proved to be successful. It appears this success at achieving the objectives, activities include: increasing knowledge and conceptual understanding of dance preparation of children and child dance technique skills for art teachers in Karanganyar District, who indicated from their success in preparing the paper / childÂ dance compilation concepts concepts and embodied in the dance of children. Key words : Preparation, Training, Dance Kids, MGMP Arts